Training on innovative topping development and digital marketing for Yammie Ayam vendors - Novi Trilisiana; Endang Mulyatiningsih; Prihastuti Ekawatiningsih; Sunarni Sunarni (Universitas Pendidikan Indonesia, 2024)
This community service program was conducted in Kapanewon Pengasih, Kulon Progo, focusing on enhancing the creativity and digital marketing skills of local mie ayam (chicken noodle) vendors. This program aimed to assist mie ayam vendors in creating innovative topping variations and expanding their market reach through digital marketing. This initiative was prompted by the limited menu variety and the vendors' lack of knowledge about online marketing, which resulted in low competitiveness and negative consumer reviews. The methods used included training in mie ayam topping development, such as teriyaki chicken, crispy fried chicken, and mushrooms, and digital marketing strategies through social media. The findings from this activity showed increased product creativity, with new topping variations favored by consumers, and an improvement in participants' ability to utilize social media for promotion. The evaluation results indicated that participants felt more confident in growing their businesses, with increased social media engagement and a rise in customers. This community service is expected to provide practical contributions to supporting the development of local culinary businesses in the digital era. Abstrak Pengabdian kepada masyarakat ini dilakukan di Kapanewon Pengasih, Kulon Progo, dengan fokus meningkatkan kreativitas dan keterampilan pemasaran digital para pedagang mi ayam lokal. Tujuan pengabdian ini adalah untuk membantu pedagang mi ayam menciptakan varian topping yang inovatif serta memperluas jangkauan pasar melalui pemasaran digital. Pengabdian ini dilatarbelakangi oleh rendahnya variasi menu dan minimnya pengetahuan pedagang tentang pemasaran online, yang berdampak pada rendahnya daya saing dan ulasan negatif dari konsumen. Metode yang digunakan meliputi pelatihan pengembangan topping mi ayam, seperti ayam teriyaki, ayam geprek, dan jamur, serta pelatihan strategi pemasaran digital melalui media sosial. Temuan dari kegiatan ini menunjukkan peningkatan kreativitas produk, dengan varian topping baru yang diminati konsumen, serta peningkatan kemampuan peserta dalam memanfaatkan media sosial untuk promosi. Hasil evaluasi menunjukkan bahwa peserta merasa lebih percaya diri dalam mengembangkan usaha mereka, dengan peningkatan interaksi di media sosial dan peningkatan jumlah pelanggan. Pengabdian ini diharapkan dapat memberikan kontribusi praktis dalam mendukung pengembangan usaha kuliner lokal di era digital. Kata Kunci: bisnis kecil; kreativitas kuliner; mie ayam; pemasaran digital